2014
DOI: 10.1097/scs.0000000000000999
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned From Two Consecutive Cleft Lip and Palate Missions and the Impact of Patient Education

Abstract: Two consecutive cleft missions were conducted in Guwahati, northeastern India in December 2010 and January 2011. In the later mission, a standardized patient education program for postoperative care was introduced. The objective of this study was to retrospectively evaluate the impact of the patient education program on cleft lip complications in terms of wound infection and dehiscence. Two hundred ninety-eight cleft lip repairs were performed in the first mission and 220 (74%) returned for early follow-up. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…For example, implementation of a standardized patient education program combining pictographs with instructions in the local language lowered postoperative infection rates during a cleft palate surgical brigade in India. 56 Additional research is needed to determine optimal modes of patient education and the effect of patient education on outcomes in these unique settings. Future efforts may even include electronic versions of materials for regions where patients have cell phone service.…”
Section: Discussionmentioning
confidence: 99%
“…For example, implementation of a standardized patient education program combining pictographs with instructions in the local language lowered postoperative infection rates during a cleft palate surgical brigade in India. 56 Additional research is needed to determine optimal modes of patient education and the effect of patient education on outcomes in these unique settings. Future efforts may even include electronic versions of materials for regions where patients have cell phone service.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 220 patients who presented for early follow-up after the first mission, 3.7% had developed lip wound infection and 9.6% developed lip dehiscence. Of the 252 patients who presented for follow up after the second mission, 0.4% had infections and 6.4% developed dehiscence [26]. Logistic regression revealed that patient education was the only covariate that contributed significantly to the decrease in wound infection rates.…”
Section: Patient-centered Carementioning
confidence: 97%
“…Cleft Lip [27] • 1 dose pre-operative intravenous antibiotic before incision Cleft Palate [28] • 1 dose pre-operative intravenous antibiotic before incision • 5 days of oral antibiotics post-operatively [30] • May breastfeed immediately; liquid diet by syringe / spoon for 1 week; soft diet for three weeks • Oral hygiene including washing mouth after eating and brushing teeth twice a day • Nothing in mouth 2. Implement standardized patient education program that is taught to nurses then to patients and families [26].…”
Section: Follow Upmentioning
confidence: 99%
“…Standardized, simple, and culturally based postoperative instructions were developed to improve the understanding of postoperative care and reduce the rate of complications. 29 Novel methods were developed to help reduce cost of follow-up care to the families. For those able to return to GC4, free local housing was provided, patients received multidisciplinary care, and travel costs were reimbursed.…”
Section: Research In a High-volume Cleft Centermentioning
confidence: 99%
“…As this model carefully ties high clinical volume with academic interests, research done through Operation Smile local centers has resulted in over 25 publications, [16][17][18][19][20][21][22][23][24][25][26] with almost 20 coming from GC4 alone. 10,[13][14][15][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Operation Smile India spent 2 preliminary years studying the government, culture, and infrastructure of Assam to develop the successful model for sustainable care that is GC4. 14,15,27 Unique methods were developed to recruit patients through nonmedical screening personnel in the community, because 87% of the population of Assam lives in rural and isolated areas.…”
Section: Research In a High-volume Cleft Centermentioning
confidence: 99%